A COMPARATIVE STUDY ON SEXUAL AND MATERNAL BEHAVIOUR OF BACTRIAN AND DROMEDARY CAMEL - NATH, K; RANJAN, R; NARNAWARE, SD; SAWAL, RK; PATIL, NV (The Indian Journal of Animal Reproduction, 2016)
The present study aimed to document the sexual and maternal behaviour of Bactrian camel and compare them with Dromedary camel. The sexual behaviour of male camel was comparable in both species except for absence of extrusion of soft pallet, absence of poll gland secretions and less vocalization and grinding of teeth in Bactrian males. The body weight loss during breeding season was more prominent in Bactrian, though poor availability of vegetation for grazing may be another contributing factor behind this observation. The copulation time in Bactrian is lesser than Dromedary camel. Estrous signs in both species were obscure. Maternal protective guarding behaviour appeared more prominent in Bactrian camel. In brief, the intensity and frequency of certain sexual and maternal behaviour vary in Bactrian and Dromedary camel though the basic features remains identical.